Philippines - Kristine May Bacatan Belbelone; Mary Angelie Gujol Arceño; Nichol Maligmat Escasinas; Louiela Jean Riño Labasano (Universitas Multi Data Palembang, 2026)
The scope of District II, Davao Oriental, Philippines, swine production plays a vital role in household income and local meat supply that supports and fosters the livelihood of the area. This study assessed the relationship between cost management and profitability among small and medium-scale swine owners. A quantitative correlational research design was applied, including 180 swine owners across the City of Mati, San Isidro, Lupon, and Banaybanay. Data was collected using a structured survey questionnaire covering feed conversion ratio, cost of production, operating margin, gross profit margin, return on investment, and return on revenue. Statistical analysis resulted in a strong, positive, and significant relationship between cost management indicators and profitability measures, where the profitability value indicates the level of statistical significance of the result of the data. The analysis indicates the importance of efficient resource allocation, efficient feed utilization, cost control, and continuous financial monitoring in sustaining a profitable swine production.